Mitoplastomic discordance in Brassicaceae phylogenomics confirms the complex evolutionary history of the family - Dominicus, Lisa J. M. A.; Al-Shehbaz, Ihsan A.; German, Dmitry A.; Mummenhoff, Klaus; Hay, Nikolai M.; Lysak, Martin A.; Koch, Marcus; Lens, Frederic; Hendriks, Kasper P. (Annals of botany, 2025)
Background and Aims The phylogeny of the Brassicaceae family has traditionally been inferred from plastid and nuclear DNA. However, early studies were limited by the availability of genetic markers and incomplete taxon sampling. Recent phylogenomic studies, leveraging more densely sampled nuclear and plastid datasets, have resolved many taxonomic uncertainties. These studies either targeted complete plastomes or provided extensive representation of the nuclear genome. Nevertheless, substantial cytonuclear discordance, poorly resolved backbone relationships and challenges in placing 'rogue taxa' have left unresolved questions about deeper relationships, notably of the five supertribes of the family. In this context, we performed the first phylogenomic analysis of the slower-evolving, maternally inherited mitogenome, which presents a promising avenue for resolving deeper phylogenetic nodes.Methods Using published mitogenomes from nine Brassicaceae species, we generated a mitogenomic reference file to recover mitogenomic sequencing read data from Hendriks et al. (2023. Global Brassicaceae phylogeny based on filtering of 1000-gene dataset. Current Biology: CB 33: 4052-4068.e6). Subsequently, we reconstructed a codon-aware mitogenomic supermatrix, alongside updated nuclear (281 genes) and plastome (76 genes) supermatrices and inferred family-wide maximum likelihood phylogenies from each of these three genomes. Congruence among the resulting phylogenies was assessed thoroughly.Key Results We present the first densely sampled family-wide mitogenomic Brassicaceae phylogeny, including 167 species, 145 genera (40% of the family) and 40 tribes (69% of the family), and the first family-wide phylogenomic comparison based on all three plant genomes. Although cytonuclear discordance was evident, we also uncovered strong phylogenomic discordance between the two organellar genomes (mitogenome and plastome), coined here as 'mitoplastomic discordance'. Our findings offer new insights into the placement of several rogue and previously unplaced taxa.Conclusions Phylogenomic discordance in Brassicaceae was more pervasive than expected. Although bifurcating phylogenies offer clear evolutionary hypotheses, they do not fully capture evolutionary complexities. Our results have implications for understanding Brassicaceae evolution, taxonomy and systematics, shedding light on processes such as hybridization and genome duplication, commonly resulting in evolutionary reticulation.
Gesehen am 06.11.2025